Analysis of the Regenerative Design of Ru porcelain in Hotels - Cui, Guolian; Taib, Mohd Zafrullah Mohd; Jamil, Azhar Abd (Al-Qadisiyah journal for engineering science, 2025)
Ru porcelain is part of China's traditional culture, and in recent years, the use of Ru porcelain as a design element of hotel space has gradually increased. The primary purpose of this study is to explore the integration of Ru porcelain and contemporary theme hotel design from the perspective of regenerative design and to create a Ru porcelain hotel space design that meets contemporary people's artistic and aesthetic characteristics. The researcher uses the dual literature research methods and case study analysis to achieve the research purpose. Literature research has meticulously combed through the concept of Ru porcelain, the redesign and innovation of Ru porcelain, and the regenerative nature of Ru porcelain in hotel design, providing reference material for scholars and practitioners. Meanwhile, the case study classifies and summarises the characteristics of Ru porcelain, the decorative elements of Ru porcelain, and the relevant examples of Ru porcelain hotels, and puts forward the regeneration design strategy of Ru porcelain hotels, emphasizing that the integration of Ru porcelain and hotels expands the development space of hotels, and will play a positive role in the improvement of the international influence of Ru porcelain culture.